Pengaruh Pendidikan Kesehatan Reproduksi pada Remaja terhadap Tingkat Pengetahuan Seksual di Mts Siulak Gedang Kabupaten Kerinci Provinsi Jambi - Dinda Aulia; Anik Purwati (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Adolescence is a transitional stage connecting childhood to adulthood, accompanied by comprehensive transformations in the biological, psychological, social, and cultural domains. This growth and development process is initiated by the manifestation of secondary sexual characteristics and progresses in a complex manner until the individual reaches the peak of reproductive maturity. This study aims to identify differences in adolescents' sexual knowledge levels before and after receiving an educational intervention. Using a one-group pretest-posttest design, this experimental study evaluated the impact of reproductive health education on the school community. The research sample was selected through purposive sampling, resulting in 54 respondents from a total population of 82 students at MTs Siulak Gedang. The data collection instrument used a structured questionnaire, which was then tested bivariately using Wilcoxon test. The study findings confirmed a significant increase in cognitive scores among respondents post-intervention, with the majority experiencing an increase in understanding to the good category. These results demonstrate that the implementation of reproductive health education is highly effective in optimizing sexual literacy among adolescents.